Muscle, Skin and Core Temperature after −110°C Cold Air and 8°C Water Treatment - Costello, Joseph Thomas; Culligan, Kevin; Selfe, James; Donnelly, Alan Edward (PLOS ONE, 2012)
The aim of this investigation was to elucidate the reductions in muscle, skin and core temperature following exposure to −110°C whole body cryotherapy (WBC), and compare these to 8°C cold water immersion (CWI). Twenty active male subjects were randomly assigned to a 4-min exposure of WBC or CWI. A minimum of 7 days later subjects were exposed to the other treatment. Muscle temperature in the right vastus lateralis (n = 10); thigh skin (average, maximum and minimum) and rectal temperature (n = 10) were recorded before and 60 min after treatment. The greatest reduction (P<0.05) in muscle (mean ± SD; 1 cm: WBC, 1.6±1.2°C; CWI, 2.0±1.0°C; 2 cm: WBC, 1.2±0.7°C; CWI, 1.7±0.9°C; 3 cm: WBC, 1.6±0.6°C; CWI, 1.7±0.5°C) and rectal temperature (WBC, 0.3±0.2°C; CWI, 0.4±0.2°C) were observed 60 min after treatment. The largest reductions in average (WBC, 12.1±1.0°C; CWI, 8.4±0.7°C), minimum (WBC, 13.2±1.4°C; CWI, 8.7±0.7°C) and maximum (WBC, 8.8±2.0°C; CWI, 7.2±1.9°C) skin temperature occurred immediately after both CWI and WBC (P<0.05). Skin temperature was significantly lower (P<0.05) immediately after WBC compared to CWI. The present study demonstrates that a single WBC exposure decreases muscle and core temperature to a similar level of those experienced after CWI. Although both treatments significantly reduced skin temperature, WBC elicited a greater decrease compared to CWI. These data may provide information to clinicians and researchers attempting to optimise WBC and CWI protocols in a clinical or sporting setting.